Prototipe Robot Penanam Benih Jagung Berbasis ESP32-CAM - Martani, Ahmad; Junaedy, Junaedy; Gogasa, Miahito (Journal of System and Computer Engineering, 2023)
Indonesia is an agricultural country, most of the population works in agriculture, planting corn is one of the activities of farmers in producing staple foods such as corn plants. However, currently farmers are still cultivating corn in the conventional way, namely using bamboo with sharpened ends to make holes in the ground to place corn seeds. This study aims to design a corn planting robot prototype with the ESP32-Cam so that farmers no longer have to use human labor to plant corn seeds. The research method used is Research and Development (R&D), Blackbox testing is used to check the functionality of each tool after the final stage of the project, whether the software or application works properly and serves its users effectively. The result of this research is a corn seed planting tool using ES32-Cam. Overall it shows that the tool can complete computerized planting work, where farmers control the tool during planting with their smartphones, namely the funnel works to remove 2 corn kernels and the depth of the planting hole is 1 – 2 cm on the surface of the soil.